Printed memtransistor utilizing a hybrid perovskite/organic heterojunction channel - Ma, C; Chen, H; Yengel, E; Faber, H; Khan, JI; Tang, M-C; Li, R; Loganathan, K; Lin, Y; Zhang, W; Laquai, F; McCulloch, I; et al. (American Chemical Society, 2021)
Neuromorphic computing has the potential to address the inherent limitations of conventional integrated circuit technology, ranging from perception, pattern recognition, to memory and decision-making ( Acc. Chem. Res. 2019, 52 (4), 964−974) ( Nature 2004, 431 (7010), 796−803) ( Nat. Nanotechnol. 2013, 8 (1), 13−24). Despite their low power consumption ( Nano Lett. 2016, 16 (11), 6724−6732), traditional two-terminal memristors can perform only a single function while lacking heterosynaptic plasticity ( Nanotechnology 2013, 24 (38), 382001). Inspired by the unconditioned reflex, multiterminal memristive transistors (memtransistor) were developed to realize complex functions, such as multiterminal modulation and heterosynaptic plasticity ( Nature 2018, 554, (7693), 500−504). Here we combine a hybrid metal halide perovskite with an organic conjugated polymer to form heterojunction transistors that are responsive to both electrical and optical stimuli. We show that the synergistic effects of photoinduced ion migration in the perovskite and electronic transport in the polymer layers can be exploited to realize memristive functions. The device combines reversible, nonvolatile conductance modulation with large switching current ratios, high endurance, and long retention times. Using in situ scanning Kelvin probe microscopy and variable-temperature charge transport measurement, we correlate the collective effects of bias-induced and photoinduced ion migration with the heterosynaptic behavior observed in this hybrid memtransistor. The hybrid heterojunction channel concept is expected to be applicable to other material combinations making it a promising platform for deployment in innovative neuromorphic devices of the future.